Economic viability of Integrated Agricultural Production Systems With consortiums in the pasture phase in Mato Grosso, Brazil - Souza, Sandra Maria Monteiro de Araujo; Gomes, Aguinaldo Rocha; Sabbag, Omar Jorge [UNESP]; Pacheco, Leandro Pereira; Wruck, Flavio de Jesus; Wingert, Gustavo; Macedo, Luis Otavio Bau; Silva, Laercio Santos; Souza, Edicarlos Damacena de (Univ Fed Rural Pernambuco, Dept Administracao, 2023)
The particularities of Integrated Agricultural Production Systems (IAPS) influence the costs of implementation and the profitability of production. However, there are few scientific approaches that seek to elucidate the total cost of SIPA in order to help make decisions about the most appropriate method to install. The purpose of this study was to propose the application of a costing method suitable for SIPA for an integrated assessment of the economic and financial viability of SIPA with single and intercropped pastures under no-till farming in Mato Grosso. Between 2015 and 2017, four types of SIPA in the pasture phase were evaluated for economic viability. Based on the cash flow, the economic viability indicators were calculated: Net Present Value (NPV), Benefit/Cost Ratio (BCI) and Internal Rate of Return (IRR). The absorption costing method allowed for a comprehensive assessment of the production costs of the SIPA, and through the apportionment criterion, indirect costs were integrated into all production activities. SIPA has different levels of profitability, depending on the grass and the consortium used. The overall net results in the 15/16 and 16/17 harvests ranged from R$ 701.81 to 1,889.01 in single pastures and from 1,435.86 to 2,129.39 in intercropped pastures. The systems showed the capacity to remunerate investments, especially when using Piata grass or a consortium between grasses and legumes with better economic indicators.
Keywords: Cerrado, Agricultural Credit. SIPA